A Comparison of Face-Down Positioning and Adjustable Positioning After Pars Plana Vitrectomy for Macular Hole Retinal Detachment in High Myopia - Gao, Yan; Ruan, Ting; Chen, Nan; Yu, Bin; Xing, Xiaoli; Du, Qing; Qi, Yan; Li, Jun (Frontiers in Medicine, 2022)
Purpose To compare the anatomical and functional outcomes of macular hole retinal detachment (MHRD) in high myopia after pars plana vitrectomy (PPV) with face-down positioning and adjustable positioning. Methods Fifty-three eyes from 53 patients with MHRD were analyzed in this study. All patients received PPV with silicon oil for tamponade and then subdivided into 2 groups: 28 were included in a face-down positioning group and 25 were included in the adjustable positioning group. Patients were followed up for at least 6 months. The main outcome was the rate of anatomical macular hole (MH) closure and retinal reattachment. Secondary outcome measures were the best-corrected visual acuity and postoperative complications. Results There was no significant difference in the rate of MH closure (53.6 vs. 72.0%, p = 0.167) and retinal reattachment (100 vs. 96%, p = 0.472) between the face-down group and adjustable group. Compared with the mean preoperative best-corrected visual acuity (BCVA), the mean postoperative BCVA at the 6-month follow-up improved significantly in both groups (p = 0, both). But there was no significant difference in the mean postoperative BCVA (p = 0.102) and mean BCVA improvement (p = 0.554) at 6 months after surgery between the two groups. There was no significant difference in the high intraocular pressure (IOP) after surgery between the two groups (53.6 vs. 44%, p = 0.487). There were no other complications that occurred during the follow-up. Conclusion Adjustable positioning after PPV with silicon oil tamponade for MHRD repair is effective and safe. Face-down positioning does not seem to be necessary for all patients with MHRD.